Eco-Friendly Technologies Based on Banana Peel Use for the Decolourization of the Dyeing Process Wastewater - Contreras-Villacura, E; Urra-Hernandez, J (2011)
This study analyzed some alternatives to the valorization of agricultural residues considering its use in the treatment of colored effluents. The acid-base behavior of the banana peel surface was thus determined in order to establish the feasibility of its use as a bioadsorbent for dyes. The adsorption capacity of Acid Black 1 was evaluated, through the equilibrium isotherm and the kinetics of this uptake process was also analyzed. Additionally, banana peel was used as substrate-support to evaluate the growth of Inonotus sp SP2, Stereum hirsutum RU 104 and Pleurotus eryngii IJFM 169 and their ligninolytic enzymes production. The decolourization ability of strain fungi was moreover screened. The concentration of functional basic groups in the banana peel surface was determined in 5.5 mmol g-1 as six and a half times higher than acid groups, while the lowest value of the maximum adsorption capacity of Acid Black 1 was 250 mg g-1. The adsorption kinetics of this dye was suitably represented by a pseudo second order model, obtaining correlation coefficients greater than 0.98. Additionally, the banana peel was demonstrated to be a source of carbon available for growth of the fungi studied. Reducing sugars supplied for banana peel were abruptly consumed up to the 5th day by S. hirsutum and Inonotus sp, while a slower consumption was observed in the case of P. eryngii. Manganese Peroxidase was produced by the three fungal strains, Inonotus sp. additionally produces Laccase and Aryl-alcohol oxidase. Screening assays showed that all of the dyes were decolorized, resulting in efficiencies between 50 and 99% by the three strains, with the exception of Basic Violet 4. Acid Black 1 was decolorized efficiently by Inonotus sp and S. hirsutum. In conclusion, banana peel is a promising material for development of an integral bioremediation strategy for wastewater containing hazardous compounds. © Springer Science+Business Media B.V. 2010.